Multiparametric FDG-PET/MRI of Hepatocellular Carcinoma: Initial Experience. (3rd October 2018) - Hectors, Stefanie J.; Wagner, Mathilde; Besa, Cecilia; Huang, Wei; Taouli, Bachir
Abstract : Purpose . To compare multiparametric (mp)FDG-PET/MRI metrics between hepatocellular carcinoma (HCC) and liver parenchyma and to assess the correlation between mpMRI and FDG-PET standard uptake values (SUVs) in liver parenchyma and HCC. Methods . This prospective, institutional review board-approved study enrolled 15 patients (M/F 12/3; mean age 61 y) with HCC. mpMRI including blood-oxygen-level-dependent (BOLD) MRI, intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI), and dynamic contrast-enhanced-(DCE-) MRI was performed simultaneously with 18 F-FDG-PET on a 3T PET/MRI hybrid system. Quantitative BOLD, IVIM and DCE-MRI parameters (Tofts model (TM) and shutter-speed model (SSM)), and PET parameters (SUVmean and SUVmax ) were quantified and compared between HCC lesions and liver parenchyma using Wilcoxon signed-rank tests. SUV ratios between HCCs and liver were also calculated (SUVmean T/L and SUVmax T/L). Diagnostic performance of (combined) mp-PET/MRI parameters for characterization of HCC was assessed using ROC analysis. Spearman correlations between PET and mpMRI parameters in HCC tumors and liver parenchyma were evaluated. Results . 21 HCC lesions (mean size 4.0 ± 2.4 cm; range 2–13 cm) were analyzed. HCCs exhibited significantly higher arterial fraction (from DCE-MRI) and lowerR 2 ∗ pre-O2 and post-O2 (from BOLD-MRI) versus liver parenchyma (P < 0.032 ). The highest diagnostic performance for differentiation between HCC and liver parenchyma was achieved for combined ART SSM andR 2 ∗ post-O2 (AUC = 0.91). SUVmax showed reasonable performance for differentiation of HCC versus liver (AUC = 0.75). In HCC, DCE-MRI parameters K trans (TM and SSM) andv e TM exhibited significant negative correlations with SUVmax T/L ( r ranges from −0.624 to −0.566; FDR-adjustedP < 0.050 ). Conclusions . Despite the observed reasonable diagnostic performance of FDG-PET SUVmax for HCC detection and several significant correlations between FDG-PET SUV and DCE-MRI parameters, FDG-PET did not provide clear additional value for HCC characterization compared to mpMRI in this pilot study.